PARTICIPANT ROLES AND PROCESS TYPES IN ENGLISH HEALTH INSURANCE FORMS (A study of Content Analysis) - Pia Nuristiana (IAIN Syekh Nurjati Cirebon, 2018)
Abstract: The paper reports on a study that investigated about the English health insurance claim form with content analysis and the systemic functional approach for the purpose of identifying process types and participant roles. According to Systemic Functional Linguistics, the experience is a process that shows â€œwhatâ€™s going onâ€ and â€œwho is involvedâ€. Thus, the experience is represented by a clause. The data consisted of 313 clauses from 5 English health insurance claim form. Results revealed five types of process, they are material, verbal, relational, mental, and existential process. Results revealed 62,9 % material process, 5,1% verbal process, 2,2% mental process, 21,4 % relational process, dan 0,9% existensial process. It means every process represents the primary elements and shows the actions.Key words: clause, giving and demanding, process types